Application of NANDA, NIC, NOC Diagnosis: Acute Pain In Improving Quality of Nursing Documentation - Rinenggantyas, Nikodimus Margo; Rofii, M; Dwiantoro, Luky (Institut Ilmu Kesehatan STRADA Indonesia, 2020)
Background: The diagnosis of pain documented in the nursing care process still needs to be evaluated. The reason is because there is still diversity in formulating the problem due to diverse nursing education, nurse knowledge, and even differences in reference standards used. Purpose: This study aimed to find out the application of diagnoses of nanda, nic, noc in improving the quality of nursing documentation.Method: This research method uses research design using descriptive analytics. The population in this study were 150 nurses in the inpatient hospital room of H.L Manambai Abdulkadir. The study sample was 73 nurses. The variable of this study is the application of diagnoses nanda, nic, noc in improving the quality of nursing documentation. Research instruments using questionnaires and statistical tests using frequency distribution.Results: The results show that the majority of nurse respondents had a female sex of 73%, and male sex numbered 27%. Based on the results of research that has been done, it was found that the majority of nurse respondents had an age of 31-40 years which was 41%, and those aged 20-30 years amounted to 32% and those aged > 40 years amounted to 27%. Based on the results of research that has been done, it was found that the majority of nurse respondents had the Application of NANDA, NIC, NOC Diagnosis in improving the Quality of Nursing Documentation by 55% and less by 45%. application of NANDA, NIC, NOC diagnoses in improving the quality of nursing documentation is good and the need for regular training to maintain it.Conclusion: From the research concluded that the use of diagnosis can improve the quality of nursing documentation